2019
DOI: 10.3390/app9071405
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to a Clock Offsets Model for Real-Time PPP Time and Frequency Transfer During Data Discontinuity

Abstract: To resolve the dilemma in any post-processing strategy, i.e., the difficulty of monitoring the real-time time and frequency signals in a timely manner, real-time GPS time and the frequency transfer have recently become trending topics. Unfortunately, data interruption occurs when conducting real-time time transfer, sometimes from unexpected reasons. In this study, to ensure the stability and precision of real-time time transfer, an adaptive prediction model and a between-epoch constraint receiver clock model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Therefore, real-time PPP applications are not reliable in their current state. Qin et al [37] solved the problem of broken communication by predicting the receiver clock offset. However, that does not solve the underlying problem, especially if internet communication is down for long periods or there is no internet at sea.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, real-time PPP applications are not reliable in their current state. Qin et al [37] solved the problem of broken communication by predicting the receiver clock offset. However, that does not solve the underlying problem, especially if internet communication is down for long periods or there is no internet at sea.…”
Section: Introductionmentioning
confidence: 99%
“…They found that fine clock coasting modeling leads to an improvement in vertical positioning precision of around 50% with only three satellites; an increase in the navigation solution availability was also observed; a reduction of holdover recovery time from dozens of seconds to only a few could be achieved. Moreover, in [15], with the aim of ensuring the stability and precision of real-time time transfer, Weijin et al proposed an adaptive prediction model and a between-epoch constraint receiver clock model; the results with the between-epoch constraint receiver clock model were smoother than those with a white noise model, as the average root mean square (RMS) values were significantly less, by at least 50%. In [16], Yiran et al investigated the time-correlated error coupled in the receiver clock estimations, proposing an enhanced Kalman filter; the RTK positioning performance was increased by a maximum of 21.40% when compared with the results obtained from the commercial low-cost U-Blox receiver.…”
Section: Introductionmentioning
confidence: 99%